Offshore wind and hybrids - A counterfactual case study for impacts in the coupled day-ahead market of Europe - Felix Jakob Fliegner; Helge Esch; Thure Traber; Marius Schrade (PLoS ONE, 2026)
Europe’s ambitious offshore wind targets hinge on the development of a single interconnected electricity market, with offshore hybrid interconnectors playing a pivotal role. These interconnectors facilitate both wind energy transmission to shore and cross-border trade, while enhancing market and grid efficiency. This study attempts to quantify these effects through a study of an additional hybrid interconnector in Europe’s present day-ahead electricity market at the example of the Baltic Sea. Using the Euphemia algorithm for single day-ahead market coupling with historical order books from 2023 and 2024, the analysis evaluates power prices, cross-border flows, and economic surplus. It applies a counterfactual “what-if” analysis to real-world market conditions which differs from commonly employed fundamental market modeling. Results reveal that a hybrid interconnector between the Baltic States and Germany would have delivered greater European welfare benefits compared to a radial wind farm connection with an independent parallel interconnector. Notably, price effects and power exchanges extend beyond the hosting countries, underscoring the need for a sea basin-wide planning and cost-sharing approach. Additionally, the distribution of surpluses between offshore producers, transmission system operators and consumers differs between radial and hybrid setups. It highlights the economic complexity and involved risk profiles introduced by offshore (hybrid) assets. This case study confirms theoretical insights from fundamental models with real-life data and identifies key considerations for decision-makers to address distributional challenges and maximize the benefits of offshore hybrid interconnectors in future planning.